ONOMATOPOEIA IN MOVIE HOW TO TRAIN YOUR DRAGON: SEMIOTIC APPROACH - Ramadhan, Wahyu Uli Afriqur; Kurniawan, Muhammad Hafiz (Universitas Putera Batam, 2022)
There were so many movies that using onomatopoeia in their script. Onomatopoeia was when the sound of a word imitated what the word referred to. One of those movies was How To Train Your Dragon. Moreover. Words can be categorized as onomatopoeia if it fulfilled a certain condition and divided into three types of onomatopoeia. However there were types of sound that explained the processes and sources of that sound of words. Because of that, this study wanted to analyze those two topics from the aspect of the references to the meaning of the signs. The data were collected and analyzed in five steps: 1) downloading the movie script from fandom.com, 2) transcribing in table of analysis, 3) analyzing the semiotic aspects of onomatopoeia using Peircian model and 4) classifying their types using Bredin’s theory and then 5) analyzing the process of onomatopoeia using semantic extension. This research found twenty one onomatopoeia that consist of thirteen direct onomatopoeia, six associative, and two exemplary. Also, the researcher have been gathered the type of sound. They were two voice – human, six voices – non-human, and twenty three noises, or sound produced by non-living this. Using these theories, onomatopoeic words can be further classified and analyzed both types and process, and these findings are expected to help the investigation of language analysis especially in analyzing onomatopoeia.